Inflammatory pathology markers (activated microglia and reactive astrocytes) in early and late onset Alzheimer disease: a post mortem study. (27th November 2017) - Taipa, R.; Ferreira, V.; Brochado, P.; Robinson, A.; Reis, I.; Marques, F.; Mann, D. M.; Melo‐Pires, M.; Sousa, N.
Abstract : Aims: The association between the pathological features of AD and dementia is stronger in younger old persons than in older old persons suggesting that additional factors are involved in the clinical expression of dementia in the oldest old. Cumulative data suggests that neuroinflammation plays a prominent role in Alzheimer′s disease (AD) and different studies reported an age‐associated dysregulation of the neuroimmune system. Consequently, we sought to characterize the pattern of microglial cell activation and astrogliosis in brain post mortem tissue of pathologically confirmed cases of early and late onset AD (EOAD and LOAD) and determine their relation to age. Methods: Immunohistochemistry (CD68 and glial fibrillary acidic protein) with morphometric analysis of astroglial profiles in 36 cases of AD and 28 similarly aged controls. Results: Both EOAD and LOAD groups had higher microglial scores in CA1, entorhinal and temporal cortices, and higher astroglial response in CA1, dentate gyrus, entorhinal and temporal cortices, compared to aged matched controls. Additionally, EOAD had higher microglial scores in subiculum, entorhinal and temporal subcortical white matter, and LOAD higher astrogliosis in CA2 region. Conclusions: Overall, we found that the neuroinflammatory pathological markers in late stage AD human tissue to have a similar pattern in both EOAD and LOAD, though the severity of the pathological markers in the younger group was higher. Understanding the age effect in AD will be important when testing modifying agents that act on the neuroinflammation.